Etymological notes on Aleut (III). With methodological notes on (Eskimo-Aleut) historical linguistics - Alonso de la Fuente, José Andrés (Servicio Editorial de la Universidad del País Vasco / Euskal Herriko Unibertsitateko Argitalpen Zerbitzua, 2011)
[EN] The goal of this contribution is twofold: on the one hand, to review two relatively recent contributions in the field of Eskimo-Aleut historical linguistics in which it is proposed that Eskimo-Aleut languages are related genealogically to Wakashan (Holst 2004) and?/or Nostratic (Krougly-Enke 2008). These contributions can be characterized by saying that their authors have taken little care to be diligent and responsible in the application of the comparative method, and that their familiarity with the languages involved is insufficient. Eskimo-Aleut languages belong to a very exclusive group of language families that have been (and still are) used, sometimes compulsively, in the business of so-called “long-range comparisons”. Those carrying out such studies are very often unaware of the most basic facts regarding the philological and linguistic traditions of those languages, as a result of what mountains of very low quality works with almost no-relevancy for the specialist grow every year to the desperation of the scientific community, whose attitude toward them ranges from the most profound indifference to the toughest (and most explicit) critical tone. Since Basque also belongs to this group of “compare-with-everything-you-come- across” languages, it is my intention to provide the Basque readership with a sort of “pedagogical case” to show that little known languages, far from underrepresented in the field, already have a very long tradition in historical and comparative linguistics, i.e. nobody can approach them without previous acquaintance with the materials. Studies dealing with the methodological inappropriateness of the Moscow School’s Nostratic hypothesis or the incorrectness of many of the proposed new taxonomic Amerindian subfamilies (several of them involving the aforementioned Wakashan languages), that is to say, the frameworks on which Krougly-Enke and Holst work, respectively, are plenty (i.a. Campbell 1997: 260-329, Campbell & Poser 2008: 234-96), therefore there is no reason to insist ...